Perspectives and challenges of educational inclusion in vulnerable childhood: A qualitative exploration - Valenzuela, Blanca Aurelia; Campa Álvarez, Reyna de los Ángeles; Guillén Lúgigo, Manuela (IE Revista de Investigación Educativa de la REDIECH, 2024)
The main objective of this research is to explore the key challenges of inclusion in public primary education in Sonora, Mexico, focusing on student diversity and vulnerable children from the teachers’ perspective. Using a qualitative approach based on symbolic interactionism, focus groups were conducted with 54 public sector teachers, exploring conceptions of educational inclusion, attention to diversity, conditions and challenges. The results underline the need to adapt educational programs for all students, regardless of their diversity, from different abilities to belonging to vulnerable groups. This comprehensive change seeks equal opportunities and promotion of academic and social development, through the adaptation of infrastructure, materials, and educational programs, and the promotion of continuous training. The importance of workshops and conferences is highlighted to develop cultural capital that promotes an inclusive culture, improve infrastructure, ensure special educational resources and form multidisciplinary teams. The challenges include equitable access, infrastructural improvements, continuous training and promotion of respect for diversity, transforming the educational system towards a more equitable and fairer one.